S‐Adenosyl‐l‐Methionine Salvage Impacts Psilocybin Formation in "Magic" Mushrooms. (10th January 2020) - Demmler, Richard; Fricke, Janis; Dörner, Sebastian; Gressler, Markus; Hoffmeister, Dirk
Abstract: Psychotropic Psilocybe mushrooms biosynthesize their principal natural product psilocybin in five steps, among them a phosphotransfer and two methyltransfer reactions, which consume one equivalent of 5′‐adenosine triphosphate (ATP) and two equivalents of S ‐adenosyl‐l ‐methionine (SAM). This short but co‐substrate‐intensive pathway requires nucleoside cofactor salvage to maintain high psilocybin production rates. We characterized the adenosine kinase (AdoK) and S ‐adenosyl‐l ‐homocysteine (SAH) hydrolase (SahH) of Psilocybe cubensis . Both enzymes are directly or indirectly involved in regenerating SAM. qRT‐PCR expression analysis revealed an induced expression of the genes in the fungal primordia and carpophores. A one‐pot in vitro reaction with the N ‐methyltransferase PsiM of the psilocybin pathway demonstrates a concerted action with SahH to facilitate biosynthesis by removal of accumulating SAH. Abstract : Maximum methylation : Psilocybin biosynthesis is completed by two successive methylations, which release S ‐adenosyl‐l ‐homocysteine (SAH) as second product. We characterized P. cubensis adenosine kinase and SAH hydrolase in vitro and show that efficient removal of SAH increases methylation and, thus, psilocybin production.